Constructing Knowledge Graphs from Text Using Large Language Models: Scoping Review - Borges Bottino, Giovanna; de Jesús Pérez Alcázar, José (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD), 2025)
The use of Large Language Models (LLMs) for Knowledge Graph (KG) construction has gained significant traction, yet the field lacks methodological standardization. This study conducts a scope review following the PRISMA framework to map existing techniques and categorize them into four main approaches: (i) RDF-Based; (ii) Prompt-Based; (iii) RAG-Based; (iv) Hybrid Pipelines. Analyzing 126 primary studies, we identify key benefits such as scalability and automation, alongside challenges like low precision and manual curation. Our findings highlight research art-state.